Introduction to Marine Dynamics - Troesch, Armin W., 1947- (Cambridge ocean technology series, 2024)
"Students will master the fundamentals of complex marine systems with this concrete introduction, linking theoretical concepts to real-world engineering applications. Includes over 60 multi-part homework problems, Matlab code, and full-colour illustrations. Ideal for senior undergraduate and graduate students in marine and mechanical engineering"--